PKM KEWIRAUSAHAAN PEMBUATAN DESSERT CUP (PUDING COKLAT) - Hikmayani Subur; Sitti Hajerah Hasyim; Ratnah S.; Abdul Rajab; Andi Tenri Ampa (CV. ALIM'SPUBLISHING, 2024)
Chocolate pudding is a food that is rich in fiber and is liked by everyone. Chocolate pudding can be made from several types of chocolate powder with various brands on the market. It is possible that the various brands of chocolate on the market have different tastes. Pudding is a colloid that is good for health, because pudding contains fiber which is good for digestion. Seeing the increasing trend of desserts, the author took the initiative to make dessert cups in order to provide education to people who want to become entrepreneurs in the culinary field, especially desserts. Dessert is not only a sweet food but also a source of nutritional content that can build energy in the body. When eating dessert makes your mood happy and your mind calm, of course the energy in your body also improves. Apart from that, this dessert made from chocolate contains antioxidants and is rich in fiber, which can fulfill the nutrients needed by the body. The methods used in this activity include lectures, questions and answers or discussions, and training. The results obtained were (1) The participants responded well to the training in making chocolate pudding dessert cups; (2) Strong motivation and interest from training participants so that it supports the transfer of information and skills from service providers to participants, and each participant can fully absorb the training material offered; and (3) The training product for making chocolate pudding dessert cups can be consumed daily and can be used as an entrepreneurial product.